Leaders facilitating innovation: leadership for innovation in a Finnish university in time of change - Ta, Thuy Ngoc (2018)
The thesis focuses on learning the experiences of leaders facilitating innovation in a Finnish university in the context of changes in the higher education sector. The study was done with the planning and data collection under the guidelines of phenomenology. The data were collected via interviewing participants with open-ended questions with six leaders who worked at different leading positions at a faculty of a Finnish university. The data were then analyzed by content analysis. The leaders were analyzed to facilitate time, communication and change to promote the innovation process at their institution. In addition, the internal factors of physical environment, collaborative leadership model, and the human factor as well as the stricter external environment were found to have impacts on the process of leadership for innovation. Regarding the complex nature of innovation, the findings indicated that the top leaders mainly promote innovation by facilitating idea generation rather than idea implementation. Related to the changes in the higher education sector in Finland, the findings suggested that the reforms limited innovation process at university. Further examinations of the results suggested the consistency of the findings to the literature of the innovation leaders’ roles, the organization climate and the human factor that drive innovation. The findings also revealed that shared leadership is related to promoting idea generation.